Chlortetracycline removal by using hydrogen based membrane biofilm reactor - Aydin, Ekrem; Sahin, Mehmet; Taskan, Ergin; Hasar, Halil; Erdem, Mehmet (Elsevier, 2016)
In the last years, increasing attention has been paid on the presence of antibiotics in aqueous environments due to their ecological damage and potential adverse effects on organisms. Membrane biofilm reactors (MBfR) have been gained a significant popularity as an advanced wastewater treatment technology in removing of organic micro-pollutants. In this study, the performance of H-2-MBfR for simultaneous removal of nitrate and chlortetracycline, formation of transformation products and community analysis of the biofilm grown on the gas permeable hollow fiber membranes was evaluated by considering effect of the hydraulic retention time, surface loadings of target pollutants and H-2 pressure. The results showed that the simultaneous chlortetracycline (96%) and nitrate removal (99%) took placed successfully under the conditions of 5 h HRT and 2 psi H-2 pressure. It has been determined that the main elimination process was biodegradation and Betaproteobacteria species was responsible for chlortetracycline degradation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Chlortetracycline; Membrane biofilm reactor; Biodegradation; Microbial community